2022
DOI: 10.32859/era.23.11.1-18
|View full text |Cite
|
Sign up to set email alerts
|

Traditional knowledge and use of wild edible plants in Sidi Bennour region (Central Morocco)

Abstract: Background: This study aimed to protect the knowledge related to the traditional uses of wild plant resources which constituted untapped potential as dietary supplements and therapeutic products Methods: An ethnobotanical survey based on the Semi-Structured Interview method was carried out among the Sidi Bennour region from February 2019 to February 2020.Results: The results showed that a total of 56 plant species representing 56 genera and 27 families were used to make different food dishes and in the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In this sense, studies carried out in Morocco have reported that C. humilis is called “Dûm” in the region of Taounat [ 77 ]. In the region of Sidi Bennour, the whole plant is also called “Eddoum” and the fruit “Lghaz” [ 78 ]. In the Middle Atlas of Morocco, the palm heart has a different name; it is called “Jmakh” [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, studies carried out in Morocco have reported that C. humilis is called “Dûm” in the region of Taounat [ 77 ]. In the region of Sidi Bennour, the whole plant is also called “Eddoum” and the fruit “Lghaz” [ 78 ]. In the Middle Atlas of Morocco, the palm heart has a different name; it is called “Jmakh” [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interest in spices and aromatic and other plants, which are natural sources of antioxidants, has increased in recent years (Aboukhalaf et al, 2020(Aboukhalaf et al, , 2022Neves et al, 2021;Mechqoq et al, 2022;Melo et al, 2022;Munekata et al, 2022;Özogul et al, 2022). Natural plant extracts are used in the food industry as alternative preservatives.…”
Section: The Preservative Effects Of Eos On Chicken and Seafood Productmentioning
confidence: 99%
“…Bekoule, a Moroccan dish containing wild food plants of species such as Lavatera trimestris , Malva spp., Rumex spp., Scolymus spp., Beta spp. (Nassif and Tanji 2013;Powell et al 2014;Bogaard et al 2018;Aboukhalaf et al 2022).…”
Section: Introductionmentioning
confidence: 99%